Radiographic foot alignment and morphological features of deltoid ligament in pediatric patients with medial osteochondral lesions of the talus. Issue 1 (January 2023) - Ikuta, Yasunari; Nakasa, Tomoyuki; Sumii, Junichi; Nekomoto, Akinori; Adachi, Nobuo
Abstract : The cause of osteochondral lesions of the talus (OLT) in patients without a history of trauma remains unclear, and almost all nontraumatic lesions appear to involve the medial talar dome. This study aimed to investigate the relationship between foot alignment, deltoid morphology, and medial OLT in pediatric patients. In total, 28 patients (31 feet) with medial OLT (17 boys, 11 girls, mean age: 14.9 years), and 50 patients without OLT (50 feet, 31 boys, 19 girls, mean age: 14.5 years) were included in this study. The OLT patients were subdivided into traumatic and nontraumatic groups. Radiographic parameters of the foot arch were measured on weight-bearing lateral images. The extent of the OLT was measured on computed tomographic images. The ratio of deep deltoid attachment length of the talus to talar height was examined as deltoid ligament position index (DPI) on coronal magnetic resonance imaging. Nontraumatic medial lesions were frequently observed in pediatric patients (54.8%) compared to traumatic lesions. The depression of the foot arch was commonly identified in pediatric patients with resistant medial lesions. The lesion size was moderately correlated with DPI (rho = 0.48; P = 0.0086). The attachment of the deep deltoid ligament to the medial talar dome was located more proximally in nontraumatic lesions than in traumatic lesions and the control group. Our findings suggest that a combination of foot alignment and the anatomic variations in the attachment of the deep deltoid ligament contributes to the incidence of nontraumatic medial OLT in the pediatric population. Level of evidence: level IV.